2020
DOI: 10.1080/0144929x.2020.1795263
|View full text |Cite
|
Sign up to set email alerts
|

Problem-based collaborative learning groupware to improve computer programming skills

Abstract: In this paper, a new computer-supported collaborative learning-based groupware is proposed for supporting problem-based collaborative learning in computer programming education setting. The geo-distributed learners can collaboratively with their tutor resolve the common programming problem within a shared workspace. The proposed system embeds some synchronous and asynchronous collaborative tools that allow learners and tutor to interact with each other to develop a shared source code of the program. This resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…This could be due to the fact that participants were mostly taking programming courses in problem-based learning environments. In recent years, problem-based collaborative learning has been considered as an important pedagogical method to be applied in computer programming learning settings (Chorfi et al., 2020). It is suggested that students were assessed based on their completion of the projects or on their program development.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the fact that participants were mostly taking programming courses in problem-based learning environments. In recent years, problem-based collaborative learning has been considered as an important pedagogical method to be applied in computer programming learning settings (Chorfi et al., 2020). It is suggested that students were assessed based on their completion of the projects or on their program development.…”
Section: Discussionmentioning
confidence: 99%
“…Collaboration is essential for ensuring impactful programming learning [22], [23]. Chorfi et al [23] argued that learning programming collaboratively requires students to work together, share skills, and learn from one another.…”
Section: Collaborative Skillsmentioning
confidence: 99%
“…Collaboration is essential for ensuring impactful programming learning [22], [23]. Chorfi et al [23] argued that learning programming collaboratively requires students to work together, share skills, and learn from one another. These activities help them learn programming better as they help build a stronger problem-solving ability [22].…”
Section: Collaborative Skillsmentioning
confidence: 99%
“…The firm had not utilized the information systems as efficiently as it has done in recent epidemic period. Thus the company could administrate the analysis of internal operations such as technological capabilities, the weaknesses of technological infrastructure, and the requirements of technological systems (Chorfi et al 2020).…”
Section: The Advantages Of Groupware Systems To Organizational Communication and Strategic Management In Covid-19 Epidemic Periodmentioning
confidence: 99%